2010
DOI: 10.1007/s00464-010-1485-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors affecting the difficulty of laparoscopic anterior resection for rectal cancer: “narrow pelvis” is not a contraindication

Abstract: Maximum tumor diameter, BMI, operator experience, and tumor location can be used to predict the operative time required to complete laparoscopic anterior resection with DST anastomosis for rectal cancer, with no correlations between pelvic dimensions and operative time. The difficulty of the procedure was not related to patients' pelvic dimensions, which led us to conclude that "narrow pelvis" is not a contraindication for this surgery. Based on these results, we suggest that laparoscopic anterior resection sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 19 publications
6
73
3
Order By: Relevance
“…Some authors have reported significant gender differences in pelvimetry measurements [20], while others have reported a significant overlap in their results and suggest that pelvimetry is a much more useful predictive tool than differences found between the sexes [21]. Tumor size, BMI, experience of the surgeon, distance of the tumor from the anal verge, dimensions of the pelvic outlet, and gender have been observed in relation to the difficulty of laparoscopic TME [6][7][8][9]. However, these studies differ considerably in their conclusions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some authors have reported significant gender differences in pelvimetry measurements [20], while others have reported a significant overlap in their results and suggest that pelvimetry is a much more useful predictive tool than differences found between the sexes [21]. Tumor size, BMI, experience of the surgeon, distance of the tumor from the anal verge, dimensions of the pelvic outlet, and gender have been observed in relation to the difficulty of laparoscopic TME [6][7][8][9]. However, these studies differ considerably in their conclusions.…”
Section: Discussionmentioning
confidence: 94%
“…However, the results of clinical studies dealing with this topic have not provided sufficiently homogeneous outcomes [6][7][8][9].…”
mentioning
confidence: 98%
“…Although no consensus exists as to the definition of a narrow pelvis, the pubiscoccyx diameter is the only pelvic diameter significantly associated with difficulties in laparoscopic total mesorectal excision. [3][4][5] Therefore, because the mean pubis-coccyx diameter has been reported to be approximately 10 cm in men, 4,5 we defined a narrow pelvis as a distance of less than 10 cm between the lower border of the pubic symphysis and the coccyx. Obesity was defined as body mass index greater than 30.…”
Section: Patientsmentioning
confidence: 99%
“…Patients were selected if they had 1 or more risk factors that would increase the difficulty of dissection of low or middle rectal cancer if a conventional laparoscopic approach were used. [3][4][5] Risk factors were defined as the presence of a narrow pelvis, a voluminous prostate, or obesity. Although no consensus exists as to the definition of a narrow pelvis, the pubiscoccyx diameter is the only pelvic diameter significantly associated with difficulties in laparoscopic total mesorectal excision.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation